Features of communication of adolescents with intellectual disabilities in the interpersonal relations - Lidiia Viktorivna Drozd; Yuliia Oleksandrivna Bystrova (Insight: the psychological dimensions of society, 2020)
The purpose of the research is theoretical justification and development of a step-by-step diagnostic program of the study of communication of adolescents with intellectual disabilities. Methods: theoretical (analysis and generalization of theoretical and methodological fundamentals of the research to identify the status of problem concerned and promising trends of its study) and empirical (psychological and pedagogical experiment to examine verbal statements, emotional responses in a conflict, ways of coping and solving challenging real-life situations, a complex of projective and objective techniques to study a personal assessment, objective reasons of conflicts and features of behavior of adolescents with intellectual disabilities in the conflict situations; comparative analysis of production and perception of statements and frustration situations) research methods. Diagnostic results show that a high level of aggressive statements or inadequate judgments and actions is common to adolescents with intellectual disabilities which correlate with a low level of socialization in the group of same-age peers and choice of behavior strategy during the conflict. It is established that adolescents with intellectual disabilities can master and comprehend communication styles in a specific context as compared to a practical situation. The paper substantiates they are characterized by impulsive actions and statements, difficulties in the catching of implication of statements, their fragmentary understanding, inability to formulate the opinion and to draw a conclusion on the obtained information, the challenges in the establishment of cause-and-effect relations, misinterpretation of interlocutor’s emotions, the transfer of communication skill to new conditions. Conclusions. The data obtained will be used in developing the program for communication correction of adolescents with intellectual disabilities as a key for their successful socialization, set and implementation of life plans.